Verdad y existencia en el Post Scriptum Kierkegaardiano: un despliegue relacional - García Aguilar, Juan Francisco (Cauriensia, 2017)
The Kierkegaardian Post Scriptum bears witness to the fact that the proper condition of the existing implies giving a meaningful scope to existence by means of an interpellating gesture. On the occasion of the interpellation, the human subject reveals his most genuine ability to inquire about the truth of himself and his happening. So the reflexive act proceeds as an attempt that seeks to make existence an event clothed with meaning. In this dynamic, there is a sustained interaction between the subject who asks and the reality that comes as a horizon capable of being signified. However, this relationship between the individual who interpellates and the reality that is happening is asymmetric, since the latter is unattainable and can surpass the attempt of the existing to mean it. In spite of this, the human subject is not totally defenseless, and resorts to his interpellant ability to make his concrete reality a fact that is admissible to be existed. In this exercise the existing confirms and challenges the true power of his thought.